Do Joint Fighter Programs Save Money? - Lorell, Mark A. (RAND Corporation, 2013)
This report analyzes costs and savings of joint aircraft acquisition programs, whether historical joint aircraft programs have saved Life Cycle Cost (LCC) over single-service programs, whether the Joint Strike Fighter is on track to achieving the originally anticipated LCC savings, and the implications of joint fighter programs for the industrial base and for operational and strategic risk.